ANALISIS PENERIMAAN PAJAK REKLAME TERHADAP PENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) KOTA MEDAN - Ginting, Felik (Fakultas Ekonomi Prodi Akuntansi, 2024)
This research was conducted at the Regional Tax and Levy Management Agency of Medan City, North Sumatra. The aim of this research is to analyze the effectiveness of the advertising tax revenue budget and the realization of advertising tax budget revenues. Apart from that, it also analyzes the contribution of advertising tax to local revenue (PAD) in Medan City. So from this analysis it can be seen whether the advertising tax has been effective in achieving the predetermined budget and has made a good contribution to Medan City's PAD. The research method used in this research is descriptive, namely the results of interviews. Interviews were conducted to find out data on the advertising tax revenue budget and the realization of the advertising tax budget from 2010 to 2015. The data analysis technique used was a survey to the research location, namely the Medan City Revenue Service office. Realization of advertising tax revenue in 2010 was 92.98% (very effective). Realization of advertising tax revenue in 2011 was 55.55% (not effective). Realization of advertising tax revenue in 2012 was 40.45% (not effective). Realization of advertising tax revenue in 2013 was 35.32% (not effective). Realization of advertising tax revenue in 2014 was 19.49% (not effective). Realization of advertising tax revenue in 2014 was 7.23% (not effective).